2011
DOI: 10.1111/j.1365-2486.2011.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian body size changes and climate change: warming or increasing variability?

Abstract: There has been a growing interest in whether established ecogeographical patterns, such as Bergmann's rule, explain changes in animal morphology related to climate change. Bergmann's rule has often been used to predict that body size will decrease as the climate warms, but the predictions about how body size will change are critically dependent on the mechanistic explanation behind the rule. To investigate change in avian body size in western North America, we used two long-term banding data sets from central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 46 publications
2
48
1
1
Order By: Relevance
“…Here, we found that wing length actually increased at a rate corresponding to 0.5% per year in females and 0.2% in males. Goodman et al [42] postulated that longer wing length might be a response to greater climatic variability or changes in primary productivity, both often described as consequences of global change that vary among biomes. Conversely, a recent study reported that cliff swallows (Petrochelidon pyrrhonota) nesting alongside a highway had reduced their wing length in a period of 30 years in order to favour agility and avoid vehicles [45], showing that selective pressures can also be local and come from unexpected sources.…”
Section: (A) Predictors Of Body Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found that wing length actually increased at a rate corresponding to 0.5% per year in females and 0.2% in males. Goodman et al [42] postulated that longer wing length might be a response to greater climatic variability or changes in primary productivity, both often described as consequences of global change that vary among biomes. Conversely, a recent study reported that cliff swallows (Petrochelidon pyrrhonota) nesting alongside a highway had reduced their wing length in a period of 30 years in order to favour agility and avoid vehicles [45], showing that selective pressures can also be local and come from unexpected sources.…”
Section: (A) Predictors Of Body Massmentioning
confidence: 99%
“…At this point, it remains unclear why the studied population showed a different trend from that of tree swallow spring migrants captured in Pennsylvania [41], and the causes of this change remain highly speculative. Nonetheless, the mechanisms proposed by Goodman et al [42] (e.g. to better resist extreme weather events such as severe storms during migration) constitute an avenue for further research.…”
Section: (A) Predictors Of Body Massmentioning
confidence: 99%
“…Long-term records have been crucial for revealing ecological patterns in response to climate change, including alterations in species' phenologies (e.g., Parmesan 2006;Pau et al 2011), changes in body size distributions (e.g., Daufresne et al 2009;Goodman et al 2012;Sheridan and Bickford 2011), and alterations in rates of ecosystem function (e.g., Traill et al 2010). Observational data have also been used to forecast the effect of climate change on biota by modelling changes in distributions under climate change scenarios (Walther et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the assumption of unidirectional changes in morphology as a response to a single environmental factor (temperature) across a wide range of species with different ecologies may be questioned, and a review of recent studies examining trends in body size produced conflicting results [16]. Birds and mammals have shown trends consistent with [12], [17], [18], and contrary to [19], [20], the prediction of decreasing body size with warmer temperatures and lower latitudes, or no clear trend [21][23]. Some studies of multiple species experiencing the same climate regime have found opposing directions of change among them [11], [16], [23], [24].…”
Section: Introductionmentioning
confidence: 99%